Growth of ordered anodic SnO2 nanochannel layers and their use for H2 gas sensing - Palacios-Padros, A.; Altomare, Marco; Tighineanu, Alexei; Kirchgeorg, Robin; Shrestha, Nabeen Kumar; Diez-Perez, Ismael; Caballero-Briones, Felipe; Sanz, F.; Schmuki, Patrik (Journal of Materials Chemistry A, 2014)
In the current work, we present a new self-organizing anodization approach of metallic Sn layers to obtain vertically aligned tin oxide nanochannel structures. For this, we use a sulphide-containing electrolyte and a set of optimized anodizing parameters. The resulting high aspect ratio nanochannel morphologies can be converted into crystalline SnO2 by high temperature annealing and show highly promising H2 sensing properties. We show that these anodic layers can operate at relatively low temperatures ( 80 °C), detecting concentrations as low as 9 ppm, and with extremely fast response and recovery times. This excellent gas-sensing performance is ascribed to the advanced structure, characterized by a crack-free, straight and top-open nanochannel geometry.
EAM Import::2019-03-13

Magnetically Guided Titania Nanotubes for Site-Selective Photocatalysis and Drug Release - Shrestha, Nabeen Kumar; Macák, Jan; Schmidt-Stein, F.; Hahn, Robert; Mierke, Claudia; Fabry, Ben; Schmuki, Patrik (Angewandte Chemie, 2008)
Quick release: The spatial and temporal delivery of active molecules (dyes or drugs) can be precisely controlled by the photocatalytic activity of TiO_2 nanotubes (see picture). The cleavage of the link between the active molecule and the nanotubes, which are filled with magnetic Fe_3O_4 nanoparticles, occurs by photoinduced chain scission under UV light; the load can be released before photodegradation by action of photogenerated radicals can occur.

MoO3 in Self-Organized TiO2 Nanotubes for Enhanced Photocatalytic Activity - Agarwal, Pankaj; Paramasivam, Indhumati; Shrestha, Nabeen Kumar; Schmuki, Patrik (Chemistry-An Asian Journal, 2010)
Self-organized nanostructures (nanotubes and nanopores) consisting of TiO_2-MoO_3 were grown on Ti-Mo substrates with different Mo contents (7 wt % Mo, 20 wt % Mo, and 35 wt % Mo) by electrochemical anodization. The photocatalytic activity of these oxide layers was compared with TiO_2 nanotubes. The results show clearly that MoO_3 doping of about 7 wt % (Ti7Mo in picture) strongly enhances the achievable photodegradation ability of titania nanotubes.
EAM Import::2019-03-12

Nickel Hydroxide Nanoparticle Activated Semi-metallic TiO2 Nanotube Arrays for Non-enzymatic Glucose Sensing - Gao, Zhi-Da; Guo, Jing; Shrestha, Nabeen Kumar; Hahn, Robert; Song, Yan-Yan; Schmuki, Patrik (Chemistry - A European Journal, 2013)
Semi-metallic TiO2 nanotube arrays (TiOxCy NTs) have been decorated uniformly with Ni(OH)2 nanoparticles without the aid of a polymer binder. The resulting hybrid nanotube arrays exhibit excellent catalytic activity towards non-enzymatic glucose electro-oxidation. The anodic current density of the glucose oxidation is significantly improved compared with traditional TiO2 nanotubes decorated with Ni(OH)2. Moreover, the Ni(OH)2/TiOxCy NT-based electrode shows a fast response, high sensitivity, wide linear range, good selectivity and stability towards glucose electro-oxidation, and thus provides a promising and cost-effective sensing platform for non-enzymatic glucose detection.
EAM Import::2019-03-08

Self-organized nano-tubes of TiO2-MoO3 with enhanced electrochromic properties - Shrestha, Nabeen Kumar; Nah, Yoon-Chae; Tsuchiya, Hiroaki; Schmuki, Patrik (Chemical Communications, 2009)
Self-organized TiO_2–MoO_3 composite oxide nano-tubes with tunable dimensions are successfully fabricated by anodization of a Ti–Mo alloy and these nano-tube layers exhibit a significantly enhanced electrochromic color contrast compared with plain TiO_2 nano-tubes.
EAM Import::2019-03-13

Self-organized TiO2 nanotubes: Visible light activation by Ni oxide nanoparticle decoration - Shrestha, Nabeen Kumar; Yang, Mingjun; Nah, Yoon-Chae; Paramasivam, Indhumati; Schmuki, Patrik (Electrochemistry Communications, 2010)
Self-organized TiO_2 nanotubes grown by anodization of Ti-substrate in a fluoride based electrolyte were loaded with Ni oxide nanoparticles by a simple chemical bath precipitation technique. The photoelectrochemical and photocatalytic activities of these nanoparticle decorated nanotubes were investigated. In comparison with the classical approaches to enhance the visible light response of TiO_2 nanotubes (N-doping), the Ni oxide loaded nanotube layers show clearly a higher visible light photoresponse and photocatalytic activity.
EAM Import::2019-03-13

Visible-light-induced photocatalysis using self-organized TiO 2 nanotubes decorated with AgBr deposits - Shrestha, Nabeen Kumar; Yang, Mingjun; Paramasivam, Indhumati; Schmuki, Patrik (Semiconductor Science and Technology, 2011)
Self-organized TiO2 nanotubes formed anodically in fluoride ion containing electrolyte were loaded with AgBr clusters from a precipitation reaction bath. The photoactivities of these nanotubes for decomposition of an azo dye were investigated under visible light irradiation and compared with those of the N-doped self-organized TiO2 nanotubes and neat TiO2 nanotubes. Compared with the N-doped nanotubes, the AgBr-loaded nanotubes demonstrate a significantly higher visible-light-driven photocatalytic activity—even higher than for neat nanotubes irradiated with UV light.
EAM Import::2019-03-12

WO3/TiO2 Nanotubes with Strongly Enhanced Photocatalytic Activity - Paramasivam, Indhumati; Nah, Yoon-Chae; Das, Chittaranjan; Shrestha, Nabeen Kumar; Schmuki, Patrik (Chemistry - A European Journal, 2010)
Mixed oxide photocatalysts: WO_3- containing TiO_2 nanotubes were prepared by self-organizing electrochemical anodization of TiW alloys (Ti 0.2 W see figure, and Ti 9 W). It is shown that a content of only 0.2 at % WO_3 with respect to the titania nanotubes leads to a very significant increase of the photocatalytic reaction rate compared not only to pure anatase TiO_2 nanotubes, but also in comparison with any other modified TiO_2 nanotube system reported up to now.
EAM Import::2019-03-12